PECULIARITIES OF TECHNOLOGY TRANSFER OF AGRICULTURAL PRODUCTION IN UKRAINE - Rasevych, I. V. (Scientific Progress & Innovations, 2021)
Transfer is a necessary tool of innovative activity existence, the goal of which is knowledge and experi-ence transfer. The stages of technology transfer in agricultural production of Ukraine have been considered in the article and the necessity of strengthening the innovation-oriented development of agrarian sector has been substantiated. The problems connected with the functioning of technology transfer networks in Ukraine have been studied. Taking into account the experience of the recent years’ innovations, it has been demon-strated that effective variants of technology transfer in agricultural production are based on the potential of scientific and educational institutions of the agro-industrial complex. It has been emphasized on the im-portance of regular state funding and support of scientific research that has a direct impact on the scientific level and quality of innovations. Practical recommendations have been given which contribute to innovative development not only in agricultural production but also influence the reformation of market infrastructure in agro-industrial complex and significantly strengthen the role of scientific and research institutions in the sphere of scientific support. Thus, it is innovative development that is the only prerequisite for ensuring eco-nomic independence of the country, which will enable to reduce the gap between our country and the devel-oped states. The current economic situation is stipulating new requirements to innovation processes. At the present time, there is a large gap in Ukraine between the requirements of science and technology and the possibilities of modern production. There is also no systemic approach to the management of innovative de-velopment and processes, which is connected with the lack of competence and instability of lawmaking activ-ities of the state bodies. Thorough management of innovative development of agricultural production has to solve these problems. It will give the chance to move a new stage of economic growth and will create favor-able conditions for the development, preservation and use of the national innovation potential.